The Hand to the Sword Like the Mind to the Word: Learning Embodied Knowledge from Late Medieval Fight Books - Leblanc, Hélène (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
Embodied knowledge is a rising concept in many fields of knowledge, and it is crucial to the field of educational sciences. This article aims to contribute to its historicization by examining the case of fight books. It takes its starting point in the coincidence suggested by Pamela Smith, between today’s notion of embodied knowledge and the pre-modern notion of art. While Smith focused on the productive arts, it is important to recognize that the pre-modern notion of art encompasses a broad spectrum, beyond craft. As such it includes fencing and the arts of combat. The article will take as case studies the three oldest known European fight books: The Liber de Arte Dimicatoria (Leeds, Royal Armouries, MS I.33); Fiore de’i Liberi’s Fior di Battaglia, and the manuscript Nuremberg, Germanisches Nationalmuseum, Cod. Hs. 3227a. The following question will guide the inquiry: What are the specific means by which Late medieval fencing, as embodied knowledge, is communicated through books?